Cocaine exposure shifts the balance of associative encoding from ventral to dorsolateral striatum - Takahashi, Yuji; Roesch, Matthew R.; Stalnaker, Thomas A.; Schoenbaum, Geoffrey (Frontiers in Integrative Neuroscience, 2007)
Both dorsal and ventral striatum are implicated in the "habitization" of behavior that occurs in addiction. Here we examined the effect of cocaine exposure on associative encoding in these two regions. Neural activity was recorded during go/no-go discrimination learning and reversal. Activity in ventral striatum developed and reversed rapidly, tracking the valence of the predicted outcome, whereas activity in dorsolateral striatum developed and reversed more slowly, tracking discriminative responding. This difference is consistent with the putative roles of these two areas in promoting habit-like behavior. Dorsolateral striatum has been directly implicated in habit or stimulus response learning, whereas ventral striatum appears to be involved indirectly by allowing cues associated with reward to exert a general motivational influence on responding. Interestingly cocaine exposure did not uniformly enhance processing across both regions. Instead cocaine reduced the degree and flexibility of cue-evoked firing in ventral striatum while marginally enhanced cue-selective firing in dorsolateral striatum. Thus cocaine exposure causes regionally specific effects on neural processing in striatum; these effects may promote the habitization of behavior by shifting control from ventral to dorsolateral regions.